Records of Grieving: Nick Cave, Phil Elverum, and the Crisis of Narration - Saarinen, Jussi A.; Boldsen, Sofie; Bogotá, Juan Diego (Topoi, 2025)
In this article, we suggest that bereavement can produce a crisis of narration: a situation where the bereaved individual needs to narrativize their grieving experience but cannot find suitable narrative resources to do so. We then argue that songwriting can provide effective self-narrative means to handle such a crisis, not only because it addresses the thematic contents of grief—e.g., suffering or longing—but also because it enables the songwriter to find fitting aesthetic form for their ongoing experience. Relatedly, we point towards a critical reconsideration of the functions that narratives have been suggested to perform in relation to grieving. To substantiate our overall proposal, we present detailed case studies of two albums—or records of grieving—that can be seen as direct self-narrative responses to bereavement: Phil Elverum’s A Crow Looked at Me and Nick Cave’s Ghosteen. In focusing not only on the content of these two lyrical narratives but also on their distinctive form and delivery, we highlight how a shift in musical-lyrical style can itself mirror and express the experience of grieving and negotiate its accompanying crisis of narration. We submit that, whereas Elverum’s songwriting functioned to express and ‘exorcise’ the essential brutality of his wife’s death, Cave’s songs enabled him to create a ‘home’ in which to reconnect with his son. Overall, we maintain that the two cases serve as noteworthy exemplars of what self-narrative practices can do in grief and as such open up valuable conceptual space for further philosophical investigations into the matter.